Perbandingan Persepsi Pasien Tuberkulosis Paru terhadap Kualitas Pelayanan Pengobatan Tuberkulosis di Puskesmas Kampung Bali dan Puskesmas Perum I di Kota Pontianak - Amiralevi, Siti Haura; Fitriangga, Agus; Ilmiawan, Muhammad In’am (Fakultas Kedokteran, Universitas Andalas, 2024)
Increasing access to quality Tuberculosis (TB) services and patient-centered care is one strategy to eliminate TB. Objective: To determined the comparison of the perception of pulmonary tuberculosis patients at the Kampung Bali Health Center and the Perum I Health Center in Pontianak City. Methods: Cross-sectional analytical observational design with total sampling method on 34 patients with details of 17 patients at the Puskesmas Kampung Bali and 17 at the Puskesmas Perum I. This research used the QUOTE-TB Light questionnaire and the Mann- Whitney comparison test as the statistical test. Results: There are no differences in the dimensions of the availability of TB services (p=0.520), communication and information (p=0.420), interaction and counseling (p=0.722), infrastructure (p = 0.608), affordability (p=1,000), and stigma (p=0,966) and there is a significant difference in the dimensions of professional competence (p=0.007). Conclusion: There is a difference in professionalcompetences. It is necessary to evaluate the competence and performances of health workers at Puskesmas Kampung Bali and Puskesmas Perum I.Keywords: Quality of TBC treatment services, patient’s perspective, QUOTE-TB Light, Tuberculosis